Manuskrip Keagamaan di Masjid Popongan: Kajian Kodikologi dan Pemetaan Isi - Gusmian, Islah (DINIKA : Academic Journal of Islamic Studies, 2019)
This article examines religious manuscripts stored in the Popongan mosque, Klaten, Central Java. As a preliminary study, this article describes the physical aspects of the manuscript as well as mapping the topics contained. The approach used is philology and historical perspective that is in it. As a manuscript born in a pesantren community, the Popongan manuscript reflects the struggle of students and scholars in the process of learning and transmission of Islamic scholarship in the late 19th century. Through the Popongan manuscripts we can see the diversity of the fields of study studied by the students and their learning methods. In this case, pesantren has taken an important role in the practice of Islamic learning and at the same time as an important subject in the history of islamization in Indonesia